Cold Shock Proteins Balance Biofilm-Associated Antibiotic Resistance and Oxidative Vulnerability in Mycobacteria - Jiachen Zheng; Linzhao He; Yizhang Wei; Jie Lu; Xiaolin Liu; Weihui Li (Microorganisms, 2025)
Cold Shock Proteins (Csps) are multifunctional regulators critical for bacterial stress adaptation. While Csps are known to regulate biofilm formation and low-temperature growth in some species, their roles in mycobacteria remain unclear. Here, we explored the functions of three Csps (CspA1, CspA2, and CspB) in Mycobacterium smegmatis. We found that CspA1 promotes biofilm formation and isoniazid (INH) resistance but negatively affects oxidative stress resistance. In contrast, CspB promotes biofilm formation, whereas CspA2 appears functionally redundant in this process. Notably, CspB and CspA2 do not contribute redundantly to oxidative stress resistance. Proteomic analysis revealed that CspA1 significantly modulates the expression of key metabolic and stress-response proteins, including WhiB3 and KatG. Our findings establish CspA1 as a key regulatory factor in mycobacteria, linking metabolic adaptation to biofilm-associated drug resistance and oxidative defense.